Exploring the relationship between neighborhood environment satisfaction and physical activity engagement among older adults a case study in Poblacion District, Davao City - Polo, Abigail T.; Rosel, Minerva C. (2021)
With the increasing growth of the elderly population, the group faces numerous physical and social role changes that challenge their capacity to live better lives. This promotes the need to support and provide the services needed by Senior Citizens. With the use of Active Aging Theory proposed by Baldassar & Atkins (2020) and the Environmental Characteristics in relation to Active Aging theory by Moran et al. (2014), this research analyzed the relationship between the satisfaction on neighborhood environment characteristics and the older adults' physical activity engagement. Through qualitative and quantitative research, the study aims to collect data that could help determine the older adults' neighborhood environment satisfaction, preferences, perceived barriers, and identify the existing neighborhood features that support or hinder the older adults from engaging in physical and social activities. The study areas in this research were in barangays with the highest percentage of elderly population in Poblacion District, Davao City. The data acquired were analyzed through Multiple Regression Analysis and Thematic Analysis. The findings from the research were used as a basis in the formulation of architectural guidelines for the proposed community center in Davao City.
Thesis(BS Architecture) --University of the Philippines Mindanao, 2021